Temporal Trends in Contemporary Use of Ventricular Assist Devices by Race and Ethnicity. (August 2018) - Breathett, Khadijah; Allen, Larry A.; Helmkamp, Laura; Colborn, Kathryn; Daugherty, Stacie L.; Blair, Irene V.; Jones, Jacqueline; Khazanie, Prateeti; Mazimba, Sula; McEwen, Marylyn; Stone, Jeff; Calhoun, Elizabeth; et al.
Abstract : Background: The proportion of racial/ethnic minorities receiving ventricular assist devices (VADs) has previously been less than expected. It is unclear if trends have changed since the broadening of access to insurance in 2014 and the rapid adoption of VAD technology. Methods and Results: Using the Interagency Registry of Mechanically Assisted Circulatory Support, we analyzed time trends by race/ethnicity for 10 795 patients (white, 67.4%; African-American, 24.8%; Hispanic, 6.3%; Asian, 1.5%) who had a VAD implanted between 2012 and 2015. Linear models were fit to the annual census-adjusted rate of VAD implantation for each racial/ethnic group, stratified by sex and age group. From 2012 to 2015, African-Americans had an increase in the census-adjusted annual rate of VAD implantation per 100 000 (0.26 [95% confidence interval, 0.17–0.34]) while other ethnic groups exhibited no significant changes (white: 0.06 [−0.03 to 0.14]; Hispanic: 0.04 [−0.05 to 0.12]; Asian: 0.04 [−0.04 to 0.13]). Stratified by sex, rates increased in both African-American men and women ( P <0.05), but the change in rate was highest among African-American men (men 0.37 [0.28–0.46]; women 0.16 [0.07–0.25]; interaction with sex P =0.004). Stratified by age group, rates increased in African-Americans aged 40 to 69 years and Asians aged 50 to 59 years ( P <0.05). The observed differential change in VAD implantation rate by age group was significant among African-Americans (interaction with age, P <0.01) and Asians (interaction with age, P =0.02). Conclusions: From 2012 to 2015, VAD implantation rates increased among African-Americans but not other racial/ethnic groups. The greatest increase in rate was observed among middle-aged African-American men, suggesting a decline in racial disparities. Further investigation is warranted to reduce disparities among women and older racial/ethnic minorities.